2018
DOI: 10.1093/jamia/ocy152
|View full text |Cite
|
Sign up to set email alerts
|

Information visualizations of symptom information for patients and providers: a systematic review

Abstract: Objective To systematically synthesize the literature on information visualizations of symptoms included as National Institute of Nursing Research common data elements and designed for use by patients and/or healthcare providers. Methods We searched CINAHL, Engineering Village, PsycINFO, PubMed, ACM Digital Library, and IEEE Explore Digital Library to identify peer-reviewed studies published between 2007 and 2017. We evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…Past research reviews found that user-preferred features (e.g., visual simplicity and familiarity) often did not result in desired outcomes, certain visual features that highlight certain aspects of risk ratios can inflate perceived risk, and that graphic representations of data did not always outperform text on riskrelated outcomes (Ancker et al, 2006). Another review found that information visualizations aimed at health-care workers were understudied and recommendations for optimizing visualization approaches were unclear given the current evidence base (Lor et al, 2019). Lipkus (2007) provided recommendations about selecting and designing graphical displays of visual information, suggesting that communicators (1) select displays for specific tasks, (2) consider the importance of accurate judgments of risk magnitude, (3) be mindful of information processing heuristics related to height/placement of information, (4) use icon arrays that group cases together, and (5) provide contextual information that explains each graph/display presented to people.…”
Section: Recommendations For Graphical Visual Contentmentioning
confidence: 99%
“…Past research reviews found that user-preferred features (e.g., visual simplicity and familiarity) often did not result in desired outcomes, certain visual features that highlight certain aspects of risk ratios can inflate perceived risk, and that graphic representations of data did not always outperform text on riskrelated outcomes (Ancker et al, 2006). Another review found that information visualizations aimed at health-care workers were understudied and recommendations for optimizing visualization approaches were unclear given the current evidence base (Lor et al, 2019). Lipkus (2007) provided recommendations about selecting and designing graphical displays of visual information, suggesting that communicators (1) select displays for specific tasks, (2) consider the importance of accurate judgments of risk magnitude, (3) be mindful of information processing heuristics related to height/placement of information, (4) use icon arrays that group cases together, and (5) provide contextual information that explains each graph/display presented to people.…”
Section: Recommendations For Graphical Visual Contentmentioning
confidence: 99%
“…Succinct data visualizations help individuals review self‐management and clinical data, facilitate communication about self‐management with healthcare providers or family, and inform decisions about self‐management behaviors. A better understanding of how individuals with T2DM perceive and interpret data visualizations may help researchers and designers to improve and optimize the use of mHealth data (Lor, Koleck, & Bakken, 2019).…”
mentioning
confidence: 99%
“…Patients need to have the opportunity to participate as true partners in their health care [ 44 ]. Utilizing user-centered participatory approaches allows the evaluation of which elements work best for which populations in which contexts [ 45 ]. Thus, application of human-centered design in health care will exponentially improve the effectiveness of medical care and disease prevention [ 43 ].…”
Section: Discussionmentioning
confidence: 99%